Freshwater diversity at a biogeographic edge zone: the high-mountain pea-clams of Ethiopia. Issue 1 (31st December 2022) - Clewing, Catharina; Geertz, Thies; Rassam, Hanane; Woldekiros, Tamirat Hailegebriel; Albrecht, Christian
Abstract : Mountain ranges are known for their particular level of biodiversity typically including a striking amount of endemism. This has been comparatively well studied for certain mountain ranges worldwide such as the Alps in Europe, the Himalayas in Asia, the Rocky Mountains in North America and the Andes in South America. Apparently, this is not the case for the mountains on the African continent and especially their freshwater fauna. One of Africa's largest high-elevated regions is the Ethiopian Highlands. The study of freshwater molluscs might potentially allow to provide valuable insights into the interplay of environmental variation and evolutionary change. Here, we present the first genetically based study of Afromontane sphaeriid bivalves in a worldwide phylogenetic framework which allowed us to assess and describe the recent diversity and endemism as well as the fauna's biogeographic background. Additionally, a new Ethiopian species of Sphaeriidae, Pisidium boessnecki Albrecht & Clewing sp. nov., could be discovered and is formally described here. Our study revealed a total of six sphaeriid species for the restricted study region in the Ethiopian Highlands of which the first two are most likely endemic: Pisidium boessnecki sp. nov., P. ethiopicum, P . cf. kenianum, P . cf. pirothi, P . cf. viridarium, and Pisidium sp. V. Based on the multigene phylogeny generated, we conclude that the observed diversity might have been caused by multiple independent colonization events from Africa. The zoogeographic affinities of all Ethiopian sphaeriids are related to the Afrotropics. The importance of these findings is discussed. http://zoobank.org/urn:lsid:zoobank.org:act:99C2C3A3-533B-4180-BBDD-E4E5A4D28F09